Developing a discovery-based guidebook for group guidance service to increase self-awareness - Bhakti, Caraka Putra; Amalia, Jihan Setyaning (International Journal on Education Insight, 2025)
Education does not only focus on developing the cognitive aspects of students but also on their social and emotional dimensions. One of the main components of self-development is self-awareness, which will help individuals understand their potential, emotions, and behavior. As adolescents navigate a transitional phase that demands greater self-awareness, group guidance services offer structured support to foster this essential developmental skill. This study aims to develop a Group Guidance Service Guidebook for the Discovery Learning Method to increase Self-Awareness in adolescents. The method used is Research and Development (R&D), with a 4D development model that includes the Define, Design, Develop, and Disseminate stages. The results of the study indicate that the developed guidebook has been considered suitable for use as a guideline for guidance and counseling teachers in providing services to students at school. Assessments by material, media, and service experts show an Aiken Index of material of 0.83, media of 0.86, and service of 0.81, all of which are included in the high category. This guide demonstrates its effectiveness in enhancing adolescent self-awareness by incorporating the discovery learning approach, which promotes active participation, personal reflection, and self-directed learning.